Surface-expressed enolase contributes to the adhesion of Paracoccidioides brasiliensis to host cells - Marcos, Caroline Maria [UNESP]; da Silva, Julhiany de Fatima [UNESP]; de Oliveira, Haroldo Cesar [UNESP]; Moraes da Silva, Rosangela Aparecida [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (Wiley-Blackwell, 2012)
Paracoccidioidomycosis is a systemic mycosis caused by the dimorphic fungus Paracoccidioides brasiliensis. Understanding the interactions between P.similar to brasiliensis and the host tissue depends on the study of the different steps of the process of colonization, especially adhesion, in which the pathogen recognizes ligands on the surface of host cells. This study aimed to verify the role of enolase in the host cellfungus interaction and the ability of enolase to bind to extracellular matrix components, to determine its subcellular localization, and to study the P.similar to brasiliensis enolase amino acid sequence. The data revealed that fibronectin is the major ligand of enolase. Evaluation of the location of enolase at an ultrastructural level revealed that it is distributed in various cellular compartments, but at a high level in the cell wall. The analysis of the amino acid sequence revealed an internal plasminogen-binding motif (254FYKADEKKY262), which is conserved in most organisms and described as an important interaction site of the enolase with the host cell surface. This suggests that enolase performs additional functions related to the glycolytic pathway and also plays a role of adhesion in P.similar to brasiliensis. Therefore, this study increases the knowledge about the characteristics of enolase and its influence on the binding process of P.similar to brasiliensis.
Keywords: Paracoccidioides brasiliensis; enolase; adhesion; extracellular matrix; immunogold